STRATEGI PEMASARAN JASA LEMBAGA PELATIHAN GARUDA TRAINING AND OUTBOUND UNTUK MENINGKATKAN MINAT MASYARAKAT MUSLIM: chicken trader marketing strategy in the market - Syahrul Chusain (J-MD Jurnal Manajemen Dakwah, 2022)
The purpose of this research in general is to find out the Marketing Strategy of Garuda Training and Outbound Training Institute Services to Increase the Interest of the Muslim Community. In detail, this research seeks to get a clear picture of: 1) Marketing Segmentation, 2) Marketing Budget, 3) Marketing Budget, and 4) Marketing Mix. The method used in this study is a descriptive method with a qualitative approach. The sources of data in this study are the Director, Operations Manager, Finance Manager, and Consumers of the Garuda Training and Outbound Training Institute. Data collection techniques used by researchers are in-depth interviews, participant and non-participant observation and documentation. In general, the results of this study conclude that the service marketing strategy carried out by the Garuda Training Institute is quite good in accordance with marketing management theory. However, there are still some shortcomings, namely in terms of time management of members. Specifically, it can be explained as follows. First, the market segmentation that has been carried out has implemented accessible groups and also differentiates these market segments by region (geography). However, the Garuda Training Institute does not divide its market segments based on demographic specifications (religion, age, gender, education level, etc.). Second, the Budgeting carried out by the Garuda Training Institute does not apply the exact amount in its budget because it adjusts from the income of previous activities and will be used for future marketing. Third, conduct marketing timings through social media only at the beginning and end of the year. Because their market segment is from the Department and Agencies. Fourth, offer the program very clearly because it lists what the program is. The prices offered are friendly to consumers' pockets and consumers can also participate in discussing prices with the Institute. The place to do marketing is also clear, namely partnering with the Bajau Hotel which is located right at the tourist spot. Promotions carried out by the Institute use promotions through social media, relations and brochures in places that are partners with the Garuda Training Institute.